Jejaring Sosial dan Resolusi Konflik Masyarakat di Pedesaan (Kasus di Pulau Saparua Provinsi Maluku) - Lala Mulyowibowo Kolopaking; Djuara Pangihutan Lubis; August Ernest Pattiselanno (Jurnal Ilmu Pertanian Indonesia, 2007)
Social networking and conflict understanding in rural community is the important step in finding strategy of conflict resolution. Through qualitative research technique, it is known that there is a relation between the flow of people who were going out-in Saparua Island to fill their needs, change into flow and networking of people who were coming home to rural areas which create conflict. All villages, so called negeri, which are known by Saparua Island community, get the impact of social networking which creates conflict. Social conflict which first based on agrarian problem then developed and added with the impact of religion and politic problem, just like conflict source in Ambon Island. Although, in the next development kinship and adat relation are taking important role in taking care of community rules. The strategy needs to be followed by establishment of natural resources and land property rights existence of society. Without this step, rural community in Saparua Island still has conflict potential. Process of this step needs to be done equal with adat relation development in Latupati Association level. With that step, rural community of this island will have social institution as a forum to have root communication. An institution which can be potency of society prevents sustainable and  long  reconflict.   Keywords: Social Networking, Conflict Resolution, Conflict in Rural Area, Saparua